Attendance allowance and disability living allowance claimants in the older population: Is there a difference in their economic circumstances? - Ruth Hancock; Marcello Morciano (University of Essex, Institute for Social and Economic Research (ISER), 2010)
The UK Disability Living Allowance (DLA) is a non-means-tested cash benefit claimable initially only by people under 65, but receipt of which can be continued after that age. The similar Attendance Allowance (AA) can only be claimed after age 65. Recent proposals for benefit reform have suggested more favourable treatment for DLA recipients, on grounds that they have longer histories of disability and consequently lower financial security. We investigate this claim using detailed survey data on household incomes and find no evidence of higher levels of income deprivation among DLA than AA recipients in terms of equivalised pre-benefit family income.
Keywords: H55; I32; 330; disability benefit; older people; social security reform; Behinderte Arbeitskräfte; Ältere Arbeitskräfte; Einkommen; Sozialtransfer; Soziale Lage; Großbritannien